INTERVENSI IRAN DALAM KONFLIK SURIAH - Ega Nurohni Sufianti; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Since 2011, the situation in Syria has become unstable due to a conflict between the government and the rebels. The conflict has attracted attention from various parties, one of which is Iran. Iran as an ally of Syria is concerned that the conflict could interfere with its interests in Syria. Therefore, Iran gave its support to the Assad regime in Syria even though Iran's own economic situation was in trouble due to the sanctions imposed by the United States and the European Union. The fundamental objective of this research is to analyze the form of Iranian intervention in the Syrian conflict, to explain the dynamics of the Syrian conflict, and to provide an overview of the diplomatic relations between Iran and Syria.This study uses a realism perspective with a level analysis of the nation state and is supported by the theory of balance of power. Balance of power can be interpreted as a mechanism that ideally makes countries intentionally or unintentionally join forces with the weaker and fight the strong.It was concluded that Iran's intervention in the Syrian conflict is divided into three, namely military aid, economic assistance and political assistance. Military assistance is then divided into four, namely advisory missions, intelligence support, weapon assistance, and troops assistance. These supports have been sent by Iran since the start of the conflict in 2011 and are expected to continue. Keywords: Bashar al-Assad, Iran, interests, intervention, Syrian conflict